4857 - Holzer, Petra (Turkey : Holzer, Petra ; Ozguven, Ethem, 2009)
A film about the working conditions in Turkey’s ship building industry. Its title, 4857, represents the number of workers who had been killed in work accidents in the past years. Addressing a rather overlooked issue, this film raises questions about global economy, industrial work ethics and labor rights.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films